A single atom change turns insulating saturated wires into molecular conductors - Xiaoping Chen (Nature Portfolio, 2021)
In molecular junctions, where a molecule is placed between two electrodes, the current passed decays exponentially as a function of length. Here, Chen et al. show that this exponentially attenuation can be controlled by changing a single atom at the end of the molecular wire.